Approaches and techniques to avoid development or progression of acute respiratory distress syndrome. Issue 1 (February 2018) - Beloncle, François; Mercat, Alain
Abstract : Purpose of review: Despite major improvement in ventilation strategies, hospital mortality and morbidity of the acute respiratory distress syndrome (ARDS) remain high. A lot of therapies have been shown to be ineffective for established ARDS. There is a growing interest in strategies aiming at avoiding development and progression of ARDS. Recent findings: Recent advances in this field have explored identification of patients at high-risk, nonspecific measures to limit the risks of inflammation, infection and fluid overload, prevention strategies of ventilator-induced lung injury and patient self-inflicted lung injury, and pharmacological treatments. Summary: There is potential for improvement in the management of patients admitted to intensive care unit to reduce ARDS incidence. Apart from nonspecific measures, prevention of ventilator-induced lung injury and patient self-inflicted lung injury are of major importance.